Co-design and Co-experimentation for Agroecological Transition: Learning from Smallholder Sheep Farmers - Mannai, Amal; Tebourbi, Ons; Ben Youssef, Salah; Zaiem, Anis; Ouerghi, Emna; Rahali, Khalil; Abdi, Bouthayna; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2024)
Current brief describes the emergence and the buildup leading to the co-design process that researchers, extension technicians and farmers lived together and went through during the set-up and the implementation of the trial assessing the effects of the mixed VOT forage (Vetch-Oat-Triticale) on sheep fertility in the Agroecology Living Landscape in Tunisia.